Structural Studies of the Lipopolysaccharide from the Fish Pathogen Aeromonas veronii Strain Bs19, Serotype O16 - Anna Turska-Szewczuk; Katarzyna A. Duda; Dominik Schwudke; Agnieszka Pekala; Alicja Kozinska; Otto Holst (Marine Drugs, 2014)
Chemical analyses, mass spectrometry, and NMR spectroscopy were applied to study the structure of the lipopolysaccharide (LPS) isolated from Aeromonas veronii strain Bs19, serotype O16. ESI-MS revealed that the most abundant LPS glycoforms have tetra-acylated or hexa-acylated lipid A species, consisting of a bisphosphorylated GlcN disaccharide with an AraN residue as a non-stoichiometric substituent, and a core oligosaccharide composed of Hep5Hex3HexN1Kdo1P1. Sugar and methylation analysis together with 1D and 2D 1H and 13C NMR spectroscopy were the main methods used, and revealed that the O-specific polysaccharide (OPS) of A. veronii Bs19 was built up of tetrasaccharide repeating units with the structure: →4)-α-d-Quip3NAc-(1→3)-α-l-Rhap-(1→4)-β-d-Galp-(1→3)-α-d-GalpNAc-(1→. This composition was confirmed by mass spectrometry. The charge-deconvoluted ESI FT-ICR MS recorded for the LPS preparations identified mass peaks of SR- and R-form LPS species, that differed by Δm = 698.27 u, a value corresponding to the calculated molecular mass of one OPS repeating unit (6dHexNAc6dHexHexHexNAc-H2O). Moreover, unspecific fragmentation spectra confirmed the sequence of the sugar residues in the OPS and allowed to assume that the elucidated structure also represented the biological repeating unit.